Imprint of parity and age at first pregnancy on the genomic landscape of subsequent breast cancer - Bastien Nguyen; David Venet; Matteo Lambertini; Christine Desmedt; Roberto Salgado; Hugo Mark Horlings; Françoise Rothé; Christos Sotiriou (Breast Cancer Research, 2019)
Abstract Background Although parity and age at first pregnancy are among the most known extrinsic factors that modulate breast cancer risk, their impact on the biology of subsequent breast cancer has never been explored in depth. Recent data suggest that pregnancy-induced tumor protection is different according to breast cancer subtypes, with parity and young age at first pregnancy being associated with a marked reduction in the risk of developing luminal subtype but not triple negative breast cancer. In this study, we investigated the imprint of parity and age at first pregnancy on the pattern of somatic mutations, somatic copy number alterations, transcriptomic profiles, and tumor immune microenvironment by assessing tumor-infiltrating lymphocytes (TILs) levels of subsequent breast cancer. Methods A total of 313 patients with primary breast cancer with available whole genome, RNA sequencing, and TILs data were included in this study. We used a multivariate analysis adjusted for age at diagnosis, pathological stage, molecular subtypes, and histological subtypes. We compared nulliparous vs. parous, late parous vs. early parous, and nulliparous vs. pregnancy-associated breast cancer (PABC) patients. Late and early parous patients were grouped by using the median age at first pregnancy. PABC was defined as patients diagnosed up to 10 years postpartum. Results Genomic alterations of breast cancer were associated with age at first pregnancy but not with parity status alone. Independently of clinicopathological features, early parous patients developed tumors characterized by a higher number of Indels (P adj = 0.002), a lower frequency of CDH1 mutations (1.2% vs. 12.7%; P adj = 0.013), a higher frequency of TP53 mutations (50% vs. 22.5%; P adj = 0.010), and MYC amplification (28% vs. 7%; P adj = 0.008). PABC were associated with increased TILs infiltration (P adj = 0.0495). Conclusions These findings highlight an unprecedented link between reproductive history and the genomic landscape of subsequent breast cancer. We further hypothesize that TP53-mutant premalignant lesions could be less susceptible to the protective effect of an early parity, which might explain the difference of parity-induced protection according to breast cancer subtypes. This work also advocates that reproductive history should be routinely collected in future large-scale genomic studies addressing the biology of female cancers.